The role of annexin A1-derived peptide Ac2–26 on liver and kidney injuries induced by cisplatin in rats - Lucchi, Danilo B.M.; Sasso, Gisela R.S.; Sena, Letícia S.; Santos, Diego D. [UNESP]; Franco, Paulo C.; Lice, Izabella; Borges, Fernanda T.; Oliani, Sonia M. [UNESP]; Gil, Cristiane D. [UNESP] (Elsevier, 2022)
Aims: In this study we evaluated the effect of pharmacological treatment with AnxA1-derived peptide Ac2–26 in an experimental model of toxicity induced by cisplatin. Main methods: Male rats were divided into Sham (control), Cisplatin (received intraperitoneal injections of 10 mg/kg/day of cisplatin for 3 days) and Ac2–26 (received intraperitoneal injections of 1 mg/kg/day of peptide, 15 min before cisplatin) groups. Key findings: After 6 h of the last dose of cisplatin, an acute inflammatory response was observed characterized by a marked increase in the number of neutrophils and GM-CSF, IL-β, IL-6, IL-10 and TNF-α plasma levels. These findings were associated with increased AnxA1 protein levels in liver and kidneys, as well as positive AnxA1/Fpr2 circulating leukocytes. Treatment with Ac2–26 produced higher levels of GM-CSF, corroborating the high numbers of neutrophils, and the anti-inflammatory cytokine IL-4. Ac2–26 preserved the morphology of liver structures and increased Fpr1 expression, preventing the damage caused by cisplatin. In the kidneys, Ac2–26 caused downregulation of renal Fpr1 and Fpr2 levels and abrogated the increased levels of the CLU and KIM-1 biomarkers of kidney damage induced by cisplatin. However, no effect of peptide treatment was detected in cisplatin-induced kidney morphology injury. Significance: Despite activation of the anti-inflammatory AnxA1/Fpr axis during cisplatin administration, treatment with Ac2–26 did not efficiently prevent its deleterious effects on the liver and kidneys.
Keywords: Formyl peptide receptors; Hepatotoxicity; Inflammation; Nephrotoxicity; Neutrophil